Molecular characteristics and pathogenic assessment of porcine epidemic diarrhoea virus isolates from the 2018 endemic outbreaks on Jeju Island, South Korea. Issue 5 (20th May 2019) - Lee, Sunhee; Lee, Dong‐Uk; Noh, Yun‐Hee; Lee, Seung‐Chul; Choi, Hwan‐Won; Yang, Hyoung‐Seok; Seol, Jun‐Ho; Mun, Seong Hwan; Kang, Won‐Myoung; Yoo, Hyekyung; Lee, Changhee
Abstract: Since the 2013–2014 incursion of the virulent G2b porcine epidemic diarrhoea virus (PEDV) pandemic strains in South Korea, frequent moderate‐scale regional outbreaks have recurred. In particular, areas of Jeju Island with extensive swine production have faced repeated epidemics since the re‐emergence in 2014. The current study reports the complete genome sequences and molecular characterization of the representative PEDV strains responsible for the 2018 endemic outbreaks on Jeju Island. All isolates were determined to belong genetically to the highly pathogenic pandemic G2b group. Full‐length genome sizes of four isolates differed from that of the G2b epidemic field strain due to insertion or deletion (DEL) mutations in the non‐structural protein (nsp)‐ or spike (S) protein‐coding regions. The 2018 Jeju isolates shared 96.7%–98.7% and 98.5%–99.4% identity at the S gene and whole‐genome levels, respectively, compared to global G2b PEDV strains. Genetic and phylogenetic analyses indicated that the 2018 isolates were closest to the 2014 G2b re‐emergent Jeju strains, but appeared to have undergone substantial rapid independent evolution. Among the isolates, a notable nsp3 DEL variant strain, KOR/KNU‐1807/2018, was isolated and propagated by continuous passages in Vero cells, and displayed typical PEDV‐induced syncytia formation. Genomic sequencing identified a unique 8‐nt DEL in the extreme C‐terminal region of the S gene at the 4th passage (KNU‐1807‐P4) compared to its original sample. This DEL resulted in the premature termination of S by nine amino acid residues (EVFEKVHVQ), which contained a KxHxx motif that is a potential endoplasmic reticulum retrieval signal. In vivo animal studies showed that variant strain KNU‐1807 had decreased virulence in suckling piglets. These results advance our knowledge regarding the genetic variation and pathogenicity of the G2b PEDV endemic strains prevalent in Jeju swine herds in South Korea.